Modern principles of prevention of anophthalmic syndrome: formation of the locomotor stump, the types of orbital implants - I. V. Zapuskalov; E. A. Gorbunova; O. I. Krivosheina (Бюллетень сибирской медицины)
This article analyzes the current state of the problem of the correction of anophthalmic syndrome. Evaluated various methods of formation of the locomotor stump after removal of the eyeball, gave a detailed description of different types of materials for the fabrication of orbital implant, as well as reflect the basic principles of prevention of complications.